PENGARUH NILAI TUKAR TERHADAP HARGA SAHAM SEKTOR PERBANKAN PADA MASA PANDEMI COVID-19 - Eka Chyntia; faisal; fauzan (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2022)
The purpose of this study was to test the exchange rate on stock prices in the banking sector during the Covid-19 pandemic. The object of this research is the stock price of banking from January to December 2020 which is represented by Bank BCA and Bank Permata. The sample in this study is the stock price of banking from January to December 2020 which is represented by Bank BCA and Bank Permata. The results showed that the exchange rate had a significant effect on the stock price of Bank BCA, but the exchange rate had no significant effect on the Bank Permata variable. Keywords: Exchange Rate, Banking Stock, BCA, Permata